Impaired Tip60-mediated Foxp3 acetylation attenuates regulatory T cell development in rheumatoid arthritis. (June 2019) - Su, Qiao; Jing, Jun; Li, Wuguo; Ma, Jianda; Zhang, Xueling; Wang, Zongren; Zhou, Zhongyang; Dai, Lie; Shao, Lan
Abstract: In rheumatoid arthritis (RA), imbalanced T cells subsets play a critical role in sustaining chronic inflammatory responses in the synovium. Naïve T cells in RA patients undergo maldifferentiation, including an increase in the effector Th1/Th17 lineage and a reduction in regulatory T (Treg) cells. Upon stimulation, naïve CD4 + CD45RO − T cells from RA patients exhibited insufficient expression of Foxp3, which induced a deficiency in Tregs production and an imbalance of Treg/Th17 differentiation. Further mechanistic study indicated that RA T cells failed to produce sufficient levels of the histone acetyltransferase Tip60, leading to reduced acetylation of Foxp3; this, in turn, decreased Foxp3 expression, impaired Treg commitment, and promoted Th17 production. Moreover, in human synovium chimeric mice, suppression of Tip60 activity in healthy T cells promoted tissue infiltration and arthritogenesis, while reconstitution of Tip60 in RA T cells suppressed synovitis and effector T cell infiltration. Our findings link T cell maldifferentiation and tissue infiltration with Tip60-mediated Foxp3 acetylation and identify Tip60 as a potential therapeutic target for suppression of tissue inflammation and autoimmunogenesis in RA. Graphical abstract: Image 1 Highlights: Acetyltransferase Tip60 expression is downregulated in the CD4 + T cells of RA patients. CD4 + T cells in RA patients have an imbalanced state between Th17/Treg cells. Tip60 insufficiency in CD4 + T of RA patients blocks Foxp3 acetylation, downregulates Foxp3 expression. Tip60-Foxp3 insufficiency in CD4 + T of RA patients decreases Treg cell and increases Th17 cell differentiation. Tip60-Foxp3 insufficiency induces T cell tissue infiltration and arthritogenesis in vivo .